Enamel erosion and prevention efficacy characterized by confocal laser scanning microscope. Issue 6 (7th April 2014) - Maia, Ana Marly Araújo; Longbottom, Christopher; Gomes, Anderson Stevens Leonidas; Girkin, John Michael
ABSTRACT The aim of this study was to evaluate the erosion‐inhibiting effect of two toothpastes on the development of erosion‐like lesions, by a confocal laser scanning microscope (CLSM). Forty human enamel blocks were divided into five groups (n = 8), in accordance to evaluate the GC MI Paste Plus and Oral B with stannous fluoride, applied as slurries and associated with toothbrush. Specimens were submitted to an erosion challenge from citric acid (0.5%, pH = 2.8), for 5 min, six times a day, alternating in artificial saliva immersions. Reference group was not exposed to treatment. Part of specimens (Groups 02 and 03) was exposed twice daily just to slurries, for 2 min, therefore specimens from Groups 04 and 05 were also abraded, for 30 s. The enamel surfaces were morphological characterized using CLSM images, with mineral loss being measured using the resulting 3D images referenced to an un‐challenged portion of the sample. Step values were compared using the one‐way ANOVA test. CLSM was shown to be a viable, noncontact, and simple technique to characterize eroded surfaces. The statistical difference in the step size was significant between the groups (P = 0.001) and using multiple comparisons a statistically significant protective effect of toothpastes was shown when these were applied as slurries. Although groups submitted to tooth brush showed mineral loss similar to reference control group, due to the damages of abrasion associated. Microsc. Res. Tech. 77:439–445, 2014. © 2014 Wiley Periodicals, Inc.